The Development Of An Intelligent Fire Alarm Detection System Using Fuzzy Logic: A Case Study - Khyrina Airin Fariza, Abu Samah (2010)
Fire is very dangerous and life threatening. Fire detection and alarm system are designed to provide warning about the outbreak of fire and allow appropriate fire fighting action to be taken before the situation gets worse and out of control. At the preliminary stage, this research reviews the current practice of detecting fire at a manufacturing company in Melaka. It is a well-known fact that high risk, damage and losses of capital will be the consequences of fire. In the fire alarm and monitoring system, the fire detector is provided with various functions. Unfortunately, the traditional fire detector does not react in the early stage of fire and is not able to differentiate between false alarm and true alarm. Due to that, fire cannot be controlled effectively and this leads to heavy losses. Therefore, through this research, the new development of intelligent fire alarm detection system using fuzzy logic has been proposed. The integration of new technologies and concepts will improve the capability of fire detection systems and enable users to discriminate between fire and non-fire threats. This will increase the time available for property and life protection.